Stereocontrolled syntheses of (-)-cubebol and (-)-10-epicubebol involving intramolecular cyclopropanation of alpha-lithiated epoxides. - Hodgson, D; Salik, S; Fox, D (2010)
Formylation of (-)-menthone (11) with LDA and HCO(2)CH(2)CF(3) avoids loss of configurational integrity at the isopropyl group, giving hydroxymethylenementhone 12. Lithium 2,2,6,6-tetramethylpiperidide-induced intramolecular cyclopropanation of derived unsaturated terminal epoxide 17 (and chlorohydrin 16), efficiently generates a substituted tricyclo[4.4.0.0(1,5)]decan-4-ol 18, which is used in a concise synthesis of (-)-cubebol (1). In contrast, isopropyl group inversion during formylation of menthone with NaOMe and HCO(2)Et led, by a similar strategy, to syntheses of 7-epicubebol (33) and (from (+)-menthone) of naturally occurring (-)-10-epicubebol (39), confirming the original structural assignment. Computational studies support the origin of the inversion as being rate-determining formylation of cis-enolate 27 from a mixture of rapidly interconverting enolates. In the synthesis of 7-epicubebol (33), allylic tertiary C-H insertion is observed as a significant competing reaction in the intramolecular cyclopropanation of unsaturated terminal epoxide 22.